Potential Medicinal Plant Antioxidant Compounds Based on Local Ethnobotany of Dadap Ayam (Erythrina variegata L.) from East OKU District - Permata, Ending; Hanum, Laila; Salni, Salni (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Indonesia is one of the countries rich in natural resources, especially plant diversity. This plant diversity includes various plants that have the potential of being traditional medicine. Types of plants that can be used in traditional medicine are useful for curing various diseases in the community and can be used as raw materials for medicine. In Ogan Komering Ulu Timur (OKU Timur) district there are 20 sub-districts but only 2 sub-districts are used as plant exploration areas that are used as observation objects, namely Bunga Mayang and Martapura. The plant surveyed is the dadap ayam plant (Erythrina variegata L.), used in traditional medicine by the Javanese people in Buay Madang Timur, OKU Timur. To determine the chemical content and antioxidant activity of the dadap ayam plant leaves. The dadap ayam plant is used in traditional medicine by the Javanese people in Buay Madang Timur, OKU Timur and is known as a herbal plant based on previous research journals. The study of the antioxidant activity of dadap ayam leaves was conducted from October to March 2025. Sampling was conducted in Bunga Mayang District, Peracak Village and Martapura District, East Ogan Komering Ulu Regency, South Sumatra. Dadap ayam leaf samples were identified at the Botany Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung (UNILA). Sample processing such as extraction, fractionation and compound purification were performed at the Genetics and Biotechnology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University (Indralaya). Metabolite profile analysis of dadap ayam leaf extract using GC-MS was conducted at the Integrated Research and Testing Laboratory, Universitas Gadjah Mada Yogyakarta. The results of this study obtained strong antioxidant activity in the thick extract of dadap ayam leaves (Erythrina variegata L.) obtained in the N-Hexane fraction, which was 5.4306 ppm and the ethyl acetate fraction, which was 17.819 ppm. The methanol-water fraction was not active in antioxidant activity. The groups of pure compounds that have antioxidant activity obtained in dadap ayam leaf samples are the terpenoid group (N1), phenol group (N2 and E1), steroid group (N3) and flavonoid group (N4, and E4). Pure compounds obtained from dadap ayam leaf samples have very strong, strong and moderate antioxidant activity. Pure compounds with the terpenoid group (N1) obtained an IC50 value of 58.49 ppm. The phenol compound group (N2 and E1) obtained an IC50 value of (17.12 ppm and 100.15 ppm). Meanwhile, the steroid compound group (N3) obtained an IC50 value of (65.59 ppm) and the flavonoid compound group (N4 and E4) obtained an IC50 value of (10.29 ppm and 25.09 ppm).